Time-based splitting strategy and forecast horizons. - Thierry Jean (20691795) (2025)
a. The test set contained the latest 7 surveys from each participant, the validation set contained the previous 7 surveys, and the training set included all (>7) earlier surveys b. Each label to predict was paired with 3 days of input data (12 6-hour periods), separately for 3 forecast horizons (same day, next day, next week).